Vibrational stark shift spectroscopy of catalysts under the influence of electric fields at electrode–solution interfaces - Bhattacharyya, Dhritiman (2021)
External control of chemical processes is a subject of widespread interest in chemical research, including control of electrocatalytic processes with significant promise in energy research. The electrochemical double-layer is the nanoscale region next to the electrode/electrolyte interface where chemical reactions typically occur. Understanding the effects of electric fields within the electrochemical double layer requires a combination of synthesis, electrochemistry, spectroscopy, and theory. In particular, vibrational sum frequency generation (VSFG) spectroscopy is a powerful technique to probe the response of molecular catalysts at the electrode interface under bias. Fundamental understanding can be obtained via synthetic tuning of the adsorbed molecular catalysts on the electrode surface and by combining experimental VSFG data with theoretical modelling of the Stark shift response. The resulting insights at the molecular level are particularly valuable for the development of new methodologies to control and characterize catalysts confined to electrode surfaces. This Perspective article is focused on how systematic modifications of molecules anchored to surfaces report information concerning the geometric, energetic, and electronic parameters of catalysts under bias attached to electrode surfaces.